The Effectiveness of Supervision by the Environmental and Forestry Agency of Central Java Province over the Rowosari Final Disposal Site from the Perspective of Agrarian Reform - Feliza, Rizka Laelya Feliza (Universitas Negeri Semarang, 2026)
This study examines the effectiveness of supervision conducted by the Environmental and Forestry Agency (DLHK) of Central Java Province over the illegal Rowosari Final Disposal Site (TPA) from the perspective of agrarian reform. The study aims to analyze the effectiveness of DLHK’s supervision and to identify the structural factors contributing to the continued operation of the illegal landfill.Using a qualitative empirical legal approach, this research combines an analysis of law in books with law in action. Data were collected through interviews, observations, and document analysis of DLHK policies and agrarian reform regulations.The findings reveal that DLHK’s supervision has not been effective, as indicated by the limited number of skilled human resources, insufficient operational budget, weak inter-agency coordination (between Provincial and Regency DLHK, the Prosecutor’s Office, and the Police), and the lack of firm enforcement measures. Agrarian reform factors further complicate resolution efforts due to conflicts over land ownership status between private rights and the social function of land, compounded by resistance from local communities managing the landfill who claim livelihood rights. The study concludes that integrated supervisory reform is necessary, including the establishment of a cross-agency Illegal Landfill Task Force; strengthening agrarian reform regulations that accommodate job relocation for affected communities; implementing tiered administrative and criminal sanctions; and digitalizing monitoring systems through GIS-based real-time supervision. Institutional strengthening of DLHK and a commitment to progressive agrarian reform are key to ensuring the permanent effectiveness of illegal landfill supervision.